2018
DOI: 10.1016/j.trre.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin, a new therapeutic for kidney transplant?

Abstract: In patients with end-stage renal disease, kidney transplantation has been associated with numerous benefits, including increased daily activity, and better survival rates. However, over 20% of kidney transplants result in rejection within five years. Rejection is primarily due to a hypersensitive immune system and ischemia/reperfusion injury. Bilirubin has been shown to be a potent antioxidant that is capable of potentially reversing or preventing damage from reactive oxygen species generated from ischemia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 92 publications
(134 reference statements)
1
38
0
Order By: Relevance
“…In patients with Gilbert syndrome (increased serum UCB levels), serum bilirubin concentration was inversely related to the levels of oxidative stress markers [32]. Clinical research shows that elevated UCB levels can reduce the expression of pro-inflammatory cytokines and increase the body's antioxidant capacity [33]. In addition, evidence from experimental studies in vitro and in vivo strongly supports the data obtained in human studies.…”
Section: Discussionmentioning
confidence: 63%
“…In patients with Gilbert syndrome (increased serum UCB levels), serum bilirubin concentration was inversely related to the levels of oxidative stress markers [32]. Clinical research shows that elevated UCB levels can reduce the expression of pro-inflammatory cytokines and increase the body's antioxidant capacity [33]. In addition, evidence from experimental studies in vitro and in vivo strongly supports the data obtained in human studies.…”
Section: Discussionmentioning
confidence: 63%
“…This was mostly reflected from the severe hyperbilirubinemia observed in the extremely rare Crigler–Najjar syndrome with levels in the 400–700 μM range, which can cause brain damage in infants [ 44 ]. The past two decades of heme oxygenase and bilirubin research has shown that bilirubin has many health benefits [ 1 , 2 , 45 ]. For instance, humans with the UGT1A1*28 Gilbert’s polymorphism that causes reduced levels of the UGT1A1 enzyme and increased plasma bilirubin levels in the 18–50 μM range [ 46 , 47 ], have been shown to have decreased incidence of cardiovascular disease [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, protection afforded by bilirubin against rejection of kidney transplantation has been demonstrated, and its antioxidant activity in preventing ischemia/reperfusion damage as well as its anti-inflammatory action that favors organ acceptance has been reviewed, highlighting the positive impact on renal hemodynamics (Sundararaghavan et al, 2018).…”
Section: Bilirubin and Ischemia/reperfusion Injurymentioning
confidence: 99%